Efektivitas Media Miniatur dalam Meningkatkan Hasil Belajar IPA Siswa Sekolah Dasar pada Materi Sistem Pencernaan Manusia - Wiga Santri Rohinia; Heny Friantary; Hengki Satrisno; Nora Safitri (MODELING: Jurnal Program Studi PGMI, 2026)
This study is a pre-experimental study aimed at examining: 1) the level of student learning interest in a class taught using a digestive system miniature model as a teaching aid; 2) the level of student learning interest in a class taught without using the digestive system miniature model; and 3) whether there is a difference in student learning interest between the class taught using the digestive system miniature model and the class taught without it. The research design employed is the Static-Group Comparison Design. The population consisted of all Grade V classes at SDN 52 Bengkulu City, comprising two classes with a total of 59 students. The sample was selected using a class-based random sampling method combined with a matching technique, resulting in two classes with a total of 34 students. Descriptive results indicate that the average learning interest score for students taught using the digestive system miniature model was 92.7648, while the score for the class not using the model was 81.2305. This demonstrates a difference in student learning interest between the class taught using the digestive system miniature model and the class taught without it.